Prevalence of Anemia among Adolescent Schools Girls of Delhi: A Cross Sectional School Based Study - Monika Singh; Om Prakash Rajoura; Raghavendra A Honnakamble (Medsci Publications, 2019)
Background: Anemia is one of the major public health problems in women of developing countries. Recent studies in India have shown that around 90% of adolescent girls are anemic. Objectives: To find the prevalence of anemia in adolescent school girls. Material and methods: It is a school based cross sectional study, in two randomly selected Government Schools of Delhi. Total of 210 adolescent girls were screened from both the schools. Dietary as- sessment and symptoms of anemia were also assessed. Results: A total of 210 girls were screened of which 203 (96.7%) were anemic. WHO criteria was used to classify anemia. Accord- ing to this criteria 93 (44.3%) were suffering from mild anemia, 101 (48.1%) moderate anemia and 9 (4.3%) were suffering from severe anemia. About 2/3rd of the study subjects (68.2%) had a history of skipping meals. History of consuming tea or coffee was very high (94.8%). Almost all (99%) of the adolescent school girls consume tea/coffee with meal or within 1 hour of taking meal. Conclusions: Anemia is highly prevalent amongst the adolescent school girls.